Surgical Treatment for Hepatocellular Carcinoma with Right Atrium Tumor Thrombus: A Literature Review - Hazmi, Mohammad Z; Syaiful, Ridho A (The New Ropanasuri Journal of Surgery, 2024)
Introduction. The prognosis of patients with hepatocellular carcinoma (HCC) with right atrial tumor thrombus (RATT) is poor, with a mortality rate of 60 to 90%. Along with the development of multimodality management and surgical techniques in cases of HCC, surgery is still an option for curative purposes. This study aims to review the indications, appropriate surgical techniques, and postoperative survival outcomes in HCC with RATT. Methods. This literature review conducted using online databases, including Cochrane Library, PubMed, ScienceDirect, EBSCOhost, and ProQuest. Results. Six case reports and four retrospective studies were reviewed. Surgery for HCC with RATT has one, three, and five–year survival rates of 34% to 53%, 14% to 26%, and 13%, with a median survival of 8 months to 26 months. Surgery with adjuvants has a five–year survival rate of up to 41% up to 12 years. However, one study stated that ionizing particle radiation had a one and three–year higher survival rate than surgery (47% and 16% compared to 34% and 14%). Conclusion. In cases of HCC with RATT, It can undergo thrombectomy through the total hepatic vascular exclusion (THVE) technique in cardiopulmonary bypass (CPB) control to prevent the release of tumor thrombus and proceed with hepatectomy. This procedure is safe and has a survival rate of 8 to 26 months